ZjHXK5 and ZjHXK6 negatively regulate the sugar metabolism of Ziziphus jujuba Mill. - Tong, Panpan; Liao, Guanglian; Lu, Dengyang; Zhou, Xiaofeng; Zhang, Wang; Xu, Qiang; Wu, Cuiyun; Wang, Jiangbo (Frontiers in Plant Science, 2024)
Hexokinase (HXK) plays a crucial role in plants, catalyzing the phosphorylation of hexose substances, which is one of the key steps in sugar metabolism and energy production. While HXK genes have been well-studied in model plants, the evolutionary and functional characteristics of HXK gene family in jujube is unknow. In this study, the HXK gene family members were identified by bioinformatics methods, the key members regulating glucose metabolism were identified by transcriptome data, and finally the function of the key genes was verified by instantaneous and stable genetic transformation. Our results showed that seven HXK genes were identified in the jujube genome, all of which were predict located in the chloroplast and contain Hexokinase-1 (PF00349) and Hexokinase-2 (PF03727) conserved domains. Most of HXK proteins were transmembrane protein with stable, lipid-soluble, hydrophilic. The secondary structure of ZjHXK proteins main α-helix, and contains two distinct tertiary structure. All ZjHXK genes contain nine exons and eight introns. Predictions of cis-regulatory elements indicate that the promoter region of ZjHXK contains a large number of MeJA responsive elements. Finally, combined with the analysis of the relationship between the expression and glucose metabolism, found that ZjHXK5 and ZjHXK6 may the key genes regulating sugar metabolism. Transient overexpression of ZjHXK5 and ZjHXK6 on jujube, or allogeneic overexpression of ZjHXK5 and ZjHXK6 on tomato would significantly reduce the content of total sugar and various sugar components. Transient silencing of ZjHXK5 and ZjHXK6 genes results in a significant increase in sucrose and total sugar content. Interestingly, the expression of ZjHXK5 and ZjHXK6 were also affected by methyl jasmonate.